Effect of Vitamin C Supplementation on Blood Lead Level, Oxidative Stress and Antioxidant Status of Battery Manufacturing Workers of Western Maharashtra, India - Ghanwat, Ganesh (J Clin Diagn Res, 2016)
INTRODUCTION: The high blood lead level induces oxidative stress and alters the antioxidant status of battery manufacturing workers. Supplementation of vitamin C is beneficial to reduce the oxidative stress and to improve the antioxidant status of these workers. AIM: The main aim of this study was to observe the changes in blood lead levels, oxidative stress i.e. serum lipid peroxide and antioxidant status parameters such as erythrocyte superoxide dismutase and catalase and serum nitrite after the vitamin C supplementation in battery manufacturing workers. MATERIALS AND METHODS: This study included 36 battery manufacturing workers from Western Maharashtra, India, having age between 20-60 years. All study group subjects were provided vitamin C tablets (500 mg/day for one month) and a blood sample of 10 ml each was drawn by puncturing the anterior cubital vein before and after vitamin C supplementation. The biochemical parameters were estimated by using the standard methods. RESULTS: Blood lead levels were not significantly altered, however, serum lipid peroxide (p<0.001, -15.56%) and serum nitrite (p<0.001, -21.37%) levels showed significant decrease and antioxidant status parameters such as erythrocyte superoxide dismutase (p<0.001, 38.02%) and catalase (p<0.001, 32.36%) revealed significant increase in battery manufacturing workers after the supplementation of vitamin C. CONCLUSION: One month vitamin C supplementation in battery manufacturing workers is not beneficial to decrease the blood lead levels. However, it is helpful to reduce the lipid peroxidation and nitrite formation and enhances the erythrocytes superoxide dismutase and catalase activity.